Mirrors of Entrapment and Emancipation : Forugh Farrokhzad and Sylvia Plath - Rahimi Bahmany, Leila (Book collections on Project MUSE., 2015)
This study explores the rich diversity of the meanings associated with the mirror and reflection in literature by women. To illustrate some of these meanings, the author draws upon the mirror imagery and the psycho-emotional experience of specular reflection in the works of the Persian poet Forugh Farrokhzad (1935-1967) and the American poet Sylvia Plath (1932-1963). These two poets astutely employed mirror images for the realization as well as for communication of their turbulent psycho-emotional states to their readers, thereby capturing and conveying the essence of women desperately trapped among the antithetical images of the twentieth-century womanhood. The impossibility of reconciling these contradictory images is manifested at times in their failure to recognize their own mirror-images. For them, the mirror becomes a heterotopic site of entrapment or a utopian space of emancipation.